The Influence of Financial Literacy and Investment Motiva-tion on Investment Interest in the Capital Market Among the Millennial Generation With Income as A Moderating Variable - Annisa Wulandari; Abdillah Arif Nasution; Ibnu Austrindanney Sina Azhar (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to analyze the influence of financial literacy and investment motivation on investment interest in the capital market among the millennial generation with income as a moderating variable. This study uses an associative research method with a quantitative approach. The population in this study is the millennial generation who have an interest in investing in the capital market, with a total of 150 respondents determined through a purposive sampling technique. Primary data was obtained through distributing questionnaires using a Likert scale, and data analysis was carried out with the help of SmartPLS 4.0 software. The results of the study indicate that financial literacy and investment motivation have a positive and significant effect on investment interest in the capital market. However, the results of the moderation test show that income only acts as a significant moderating variable in strengthening the relationship between financial literacy and investment interest. Meanwhile, income does not significantly moderate the relationship between investment motivation and investment interest. These findings provide important implications for policy makers and financial institutions to improve financial literacy through comprehensive education programs and consider the income aspect in encouraging investment interest.